2004
DOI: 10.1667/rr3144
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the X-Radiation, Drug and Ultraviolet-Radiation Responses of Clones Isolated from a Human Colorectal Tumor Cell Line

Abstract: We isolated several clones with a wide range of responses to X radiation from an unirradiated human colorectal (HCT 116) tumor cell line. The responses of one of these clones (HCT116-Clone10) and nine other clones to either fractionated or acute (i.e. single, nonfractionated doses) X irradiation in vitro was similar to that of the parental cell line. By contrast, after the same types of treatment, another clone (HCT116-Clone2) manifested a significantly increased survival whereas a third clone (HCT116-CloneK) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…This may also be true for heterogeneous and genetically instable clinical tumor samples exposed to radiation. [54][55][56] Most experimental facts concerning the biology of MC are based on observations obtained using cells growing in monolayer, and even if these may serve well as models, extrapolation to three-dimensional in vivo structures should be done with great consideration. 57 In fact, specific cell-cell and cell-matrix interactions may be as important as the genomic background for the MC response, although this point of view is frequently neglected.…”
Section: Dna Damage-induced MCmentioning
confidence: 99%
“…This may also be true for heterogeneous and genetically instable clinical tumor samples exposed to radiation. [54][55][56] Most experimental facts concerning the biology of MC are based on observations obtained using cells growing in monolayer, and even if these may serve well as models, extrapolation to three-dimensional in vivo structures should be done with great consideration. 57 In fact, specific cell-cell and cell-matrix interactions may be as important as the genomic background for the MC response, although this point of view is frequently neglected.…”
Section: Dna Damage-induced MCmentioning
confidence: 99%
“…This was because these radiationresistant or -sensitive clones were closely related genetically but differed only in their XR-resistance or -sensitivity (9). However, our cDNA microarray results have demonstrated that at least up to 24 h after XR treatment with an acute dose of 4 Gy, which would have killed more than 50% of the cells in all the 3 clones used in our studies (9), there was no significant up-regulation or down-regulation of the majority of known DNA damage sensor/repair, cell cycle, and or apoptosis related genes in either clone when each was individually compared to the control clone with the same radiation response as the parental HCT116 cells. Instead, our results suggested potentially novel genes, or even new pathways, that may or may not interact with the known DNA damage response routes (detection, repair, cell cycle, apoptosis) that can putatively lead to sensitivity or resistance to XR (1).…”
Section: Discussionmentioning
confidence: 80%
“…Clone2_XRR , HCT116 CloneK_XRS and HCT116 Clone10_control were all isolated at the same time (9). HCT116 Clone2_XRR and HCT116 CloneK_XRS were subsequently characterized as an XR-resistant and XR-sensitive clone (relative to the parental HCT116 cell line), respectively.…”
Section: Isolation Of Hct116 Clones With Different Xr Response Phenotmentioning
confidence: 99%
See 2 more Smart Citations